Night in Werewolf woods - Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1996)
Your family is going on vacation to WoodsWorld cabins. Rumor has it that terrifying creatures roam the woods at night. Can you survive until sunrise.
"An Apple paperback."
"A Parachute Press book."
Choose from over 20 different scary endings!--Cover.
Keywords: Horror tales; Plot-your-own stories; Plot-your-own stories; Horror stories, American; Werewolfs -- Fiction